Neoadjuvant chemotherapy in urothelial bladder cancer: impact of regimen and variant histology. (August 2016) - Kaimakliotis, Hristos Z; Monn, M Francesca; Cho, Jane S; Pedrosa, Jose A; Hahn, Noah M; Albany, Costantine; Gellhaus, Paul T; Cary, K Clint; Masterson, Timothy A; Foster, Richard S; Bihrle, Richard; Cheng, Liang; et al.
Aim: We compared the efficacy of methotrexate/vinblastine/doxorubicin/cisplatin (MVAC) versus gemcitabine/cisplatin in urothelial cancer and neoadjuvant chemotherapy (NACT) efficacy in variant histology (VH).Materials & methods: Radical cystectomy patients were retrospectively compared with those who received NACT. Factors associated with survival, pathologic complete response (pCR) and downstaging (pDS) were evaluated in multivariable models.Results: 9% of radical cystectomy patients (84/919) received NACT, with improved survival, pCR and pDS on both regimens. MVAC lead to higher pDS without an increase in pCR. On multivariable analysis, there was a nonsignificant increase in pDS with MVAC. NACT conferred similar responses in squamous and glandular differentiation VH.Conclusion: NACT was associated with improved survival, pCR and pDS. Furthermore, responses to NACT were not dependent on presence of VH.